LITERATURE REVIEW METODE PENGOLAHAN CITRA PADA UDANG DAN IKAN: LITERATURE REVIEW METODE PENGOLAHAN CITRA PADA UDANG DAN IKAN - zul, zulfaqar; Ananda; Memen Akbar (Politeknik Negeri Bengkalis, 2023)
Information technology has indeed brought great changes in human life. Shrimp is one of the main products of aquaculture in Indonesia and is also an export product to various countries, namely the United States, the European Union, Japan, and several countries in the Asian region, shrimp commodity exports that provide foreign exchange for the country are in the form of frozen shrimp, fresh shrimp. Body weight and length are important biological indicators and specifications in the growth and maturity of shrimp. In calculating shrimp body weight and length, this study will discuss a comparison of several methods, image retrieval, and results from each researcher. From these articles is that image processing and Machine Learning / Deep Learning techniques are used effectively to detect, measure, and classify various aspects of shrimp and fish in underwater environments. Some methods managed to achieve high accuracy in these tasks, but challenges remain such as the effects of background noise and variations in the water environment.